TO THE CALCULATION OF THE PARAMETERS OF THE ATTACHMENTS OF THE FRONT AND REAR PARTS OF THE PLOW ACCORDING TO THE "PUSH-PULL" SYSTEM (Conference Zone, 2022)
In the world, the leading place is occupied by the improvement of tillage machines and units, as well as the use of advanced technologies and modern technical means for cultivating crops, obtaining high yields from them while maintaining soil fertility. If we take into account that “more than 1.8 billion hectares of land are cultivated annually in the world for the cultivation of various agricultural crops,” then one of the most important tasks is the development of energy-saving tillage machines and tools with high quality work and productivity. In countries developed in this direction, including the USA, Germany, Holland, England, Italy, the Russian Federation, Belarus, Ukraine and others, certain successes have been achieved, where special attention is paid to the use of plows, combined machines and working bodies for the main and pre-sowing tillage according to the “push-pull” system (push-pull), i.e. tillage machines, consisting of working parts mounted on the tractor in front and behind.